2022
DOI: 10.1097/mao.0000000000003491
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Statement on Bone Conduction Devices and Active Middle Ear Implants in Conductive and Mixed Hearing Loss

Abstract: Nowadays, several options are available to treat patients with conductive or mixed hearing loss. Whenever surgical intervention is not possible or contra-indicated, and amplification by a conventional hearing device (e.g., behind-the-ear device) is not feasible, then implantable hearing devices are an indispensable next option. Implantable bone-conduction devices and middle-ear implants have advantages but also limitations concerning complexity/invasiveness of the surgery, medical complications, and effectiven… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
1
22
0
5
Order By: Relevance
“…When testing the relationship between speech hearing dimension in the SSQ and the result of speech tests with the new AP, a significant negative correlation was obtained for S0-N0; a smaller (also negative) but not significant correlation for S0-N180, and no correlation for WRS obtained in quiet. A similar relationship was noted by Remakers et al, who found, using SSQ, a significant (but weak to moderate) negative correlation between the subjective test results of the speech hearing dimension and the related objective speech perception in noise test [35]. In the recently published 'Consensus Statement on Bone Conduction Devices and Active Middle Ear Implants in Conductive and Mixed Hearing Loss', the authors address an important issue, noting that companies introducing new processors should enable patients with older implants to reap the benefits of new features and signal processing developments [36].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…When testing the relationship between speech hearing dimension in the SSQ and the result of speech tests with the new AP, a significant negative correlation was obtained for S0-N0; a smaller (also negative) but not significant correlation for S0-N180, and no correlation for WRS obtained in quiet. A similar relationship was noted by Remakers et al, who found, using SSQ, a significant (but weak to moderate) negative correlation between the subjective test results of the speech hearing dimension and the related objective speech perception in noise test [35]. In the recently published 'Consensus Statement on Bone Conduction Devices and Active Middle Ear Implants in Conductive and Mixed Hearing Loss', the authors address an important issue, noting that companies introducing new processors should enable patients with older implants to reap the benefits of new features and signal processing developments [36].…”
Section: Discussionsupporting
confidence: 85%
“…Dornhofer et al, in a group of 95 hearing aid users, correlated aided audiological measures (PTA, Nu-6, SPIN) with aided APHAB subscales and global score; they saw no significant relationship. Absent or low correlations between patient self-reported scores and speech recognition have also been reported among cochlear implant users [33][34][35]. Mertens et al reported that self-assessment tools, like SSQ, offer insights into dynamic hearing capacities that cannot be easily measured in the laboratory and provide useful information about the hearing status of CI users [33].…”
Section: Discussionmentioning
confidence: 99%
“…Along with their development, audiologists and otologists have sought and experimented with new applications for these implantable devices. Currently, however, there is no universal agreement in the scientific literature 1 . Congresses, meetings, conferences, and consensus statements have been organised internationally to achieve this goal.…”
Section: Introductionmentioning
confidence: 99%
“…It provides a first framework for clinical, surgical, and audiological procedures on implantable devices. The aim was to deliver a technical characterisation of these devices to enhance effective communication between the various stakeholders, and thus improve health care 1 . The consensus underlines that the scientific literature does not lead to comprehensive results for these devices.…”
Section: Introductionmentioning
confidence: 99%
“…In individuals with unilateral hearing loss, including SNHL, mixed hearing loss, and CHL types, bone conduction devices (BCDs) have been employed as effective tools for hearing rehabilitation [16,17]. When conventional BCD was first created in the early 20 th century, it was transcutaneous [18].…”
Section: Introductionmentioning
confidence: 99%